Al-Hafiz Al-Zarkasyi Dan Kitabnya Al-Nukat 'Ala Muqaddimah Ibn Al-Salah - Zulhilmi Mohamed Nor; Ahmad Sanusi Azmi (Universiti Sains Islam Malaysia, 2024)
Introduction to the Science of Hadith is one of the masterpieces works produced by a prominent scholar of hadith, Ibn al-Salah al-Shahrazuri. This works is considered as a major source in the study of hadith terminology and its sciences. Due to its importance, a number of works have been authored based upon or derived from the content conferred in Muqaddimah of Ibn Salah. Al-Hafiz Badr al-Din al-Zarkashi was among them. He composed a specific explanation on Ibn Salah's Muqaddimah entitled al-Nukat 'Ala Muqaddimah Ibn al-Salah. This study aims to expound the intellectual beckground of al-Zarkashi, and explore his academic enterprise in elucidating Ibn Salah's notion through his work al-Nukat. It also seeks to scrutinise al-Zarkashi's unique methods and approaches in understanding the sciences of hadith.